PERAMALAN CURAH HUJAN EKSTREM DI KOTA MEDAN DENGAN MODEL SPATIAL EXTREME VALUE DENGAN PENDEKATAN MAX STABLE PROCESS - Atika Nadila; Machrani Adi Putri Siregar (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2023)
This research includes extreme spatial values. Application of the method with the Max-Stable (MSP) process. The approach will be used for the analysis of extreme rainfall in Medan City and Deli Serdang Regency. The extreme value sample selected by the Block Maxima Method, will be estimated to the spatial extreme value form by including location factors. The Max Stable Process (MSP) is an extension of the Multivariate distribution of extreme values into an infinite dimension of the theoretical extreme values. After selecting the best model, extreme rainfall data in Medan City and Deli Serdang Regency were obtained, then calculating predictions of extreme rainfall with certain time periods. Predictions are calculated using the rate of return, predictions of extreme rainfall using the return period for the next two years, in the city of Medan Belawan Maritime Station will reach 122.98 mm, BMKG Region 1 Station will reach a value of 139.13 mm. And the rain monitor in Deli Serdang Regency, the Deli Serdang Geophysics Station is predicted to be a maximum of 218.09 mm, the Kualanamu Meteorological Station is predicted to reach 91.87 mm, the North Sumatra Climatology Station will reach a maximum value of 174.18 mm. Predicted maximum Precipitation extremes can also be calculated for t (time) in future periods